Implementasi Schedule Waktu dalam Layanan Klasikal Guna Membentuk Disiplin Waktu Siswa Kelas XI SMA YPK Medan - Dara Adiba Latersia Gintin; Uli Makmun Hasibuan; Mey Syandry Khairunnisa; Irna Tri Aulia Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze how the implementation of time schedules in classical services can form time discipline in class XI students at SMA YPK Medan. Through a qualitative approach, data were collected using observation, interview, and documentation techniques to gain an in-depth understanding of the process of implementing time schedules. The results of the study indicate that the consistent implementation of time schedules in classical services can increase students’ awareness of the importance of time discipline in learning activities and other school activities. In addition, the involvement of teachers and counselors in providing routine guidance and supervision is a major supporting factor in forming students’ time discipline behavior. Obstacles that arise, such as lack of motivation and supervision from the surrounding environment, can be overcome through collaboration between the school, students, and parents. Thus, the implementation of time schedules in classical services has proven effective in forming time discipline in class XI students at SMA YPK Medan.